Análise morfológica, física e química de duas ocorrências erosivas lineares de grande porte no município de Morrinhos (GO) - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The city of Morrinhos, is located to the state of Goiás South has its economy based on agriculture, with a focus on rainfed agriculture and irrigated sugar cane, soybeans, corn, tomatoes, beans, as well as livestock. The characteristics of the physical environment has flat relief to gently rolling, deep soils with medium texture to clayey and humid sub tropical climate with two distinct seasons, a rainy, from October to April and a dry season from May to September encourage such economic activities. The types of uses and soil management such use when they do not obey the natural limitations have contributed to the emergence of large linear erosions in the city, causing loss of soil and silting of local and regional drainage. The research aimed to diagnose the causes of two gullies emergence in different river basins in the rural area of the municipality, aimed to identify the erosive mechanisms controlling its development, to propose appropriate containment measures. The survey was conducted from literature review, registration and field work at Fazenda Serra and Fazenda Mimoso: a) characterization of the incisions, dimensions, shape and characteristics of the physical environment of the catchment area, b) identification of the erosive mechanisms that govern its dynamics, c) development of toposequence; d) morphological description of the field in soils; e) collection of deformed soil samples for physical analysis of texture and routine chemistry; e) conventional photographic records and aerial shots with Drone DSI Phantom 2. In another step, they were prepared thematic maps (location, geology, geomorphology, hypsometry, slope, soils, hydrology, land use and occupation and erosion susceptibility) which allowed a better understanding of the relationship between the type of land use and the characteristics of the environment physical of each contribution area, the development of gullies investigated. The gully of Vendinha is located west of the municipal headquarters, 11 km from the city center to 670m altitude. It appeared runoff from a side road, which concentrates the storm water runoff toward a water receiving area. It is unstable, with eroded slopes, temporary pipings and widespread mass movements. The gully Mimoso is located at an elevation of 804m. It refers to the reactivation of a natural erosion induced by human activities in pasture area. It has unstable stretches of occurrence of mass movements at points of very steep slopes. However, it shows signs of stabilization with spontaneous repopulation with typical vegetation of wetlands or riparian vegetation. To containing gullies is suggested: a) surrounding the insulated wire fence; b) planting native tree species within the incisions; c) planting grasses and bamboos on the banks and within the gullies; d) construction of cross palisades to its main axis; e) continuous monitoring of implemented interventions; f) alternative use of these áreas.A characterization of soils affected by erosion concludes that erosion has texture Franco clayey and Sandy and in return the other Franco clayey and clayey, the chemical characteristics more clayey has higher nutrient availability, and ease of repopulation induced complicated fact the sandy erosion.
Keywords: Voçorocas; Descrição morfológica; Erosões lineares; Gullies; Morphological description; Linear erosions; CIENCIAS BIOLOGICAS